Tindak Pidana Kekerasan Seksual dalam Perspektif Hukum Positif dan Hukum Islam: Sebuah Telaah Berbasis Sejarah Sosial Islam - Adinda, Nendena Rizqi; Rosadi, Aden; Naisabur, Nanang (Sharia Journal and Education Center Publishing, 2025)
Sexual violence crime (TPKS) is a crucial issue in Indonesia, which received a significant response through the enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS). This research aims to critically and deeply compare the concept of TPKS in Indonesian Positive Law (UU TPKS) and Islamic Law (Fiqh Jinayah), reinforced by the foundation of Islamic Social History. Positive Law, through the UU TPKS, adopts a progressive and victim-centered framework, expanding the definition of offense to include non-physical harassment and sexual exploitation, and emphasizing the principle of lack of consent. This Law guarantees the rights to recovery, restitution, and assistance, although its implementation still faces structural and cultural obstacles, including the risk of secondary victimization and issues in proof. Meanwhile, Fiqh Jinayah classifies sexual violence into several categories: Jarimah Hudud (such as zina or fornication, though the victim of rape is exempted from the hadd punishment due to coercion), Ightishab (rape) which can be equated with Hirabah (brigandage), and Jarimah Ta’zir (for broader offenses). Although the standard of proof for zina in classical view is very strict (four witnesses), modern scholars tend to accept non-traditional evidence for ightishab (such as medical examination/visum and victim's testimony) to impose a firm ta’zir punishment. The analysis of Islamic Social History affirms that Islamic legal norms regarding sexual protection are dynamic, stemming from efforts to eliminate pre-Islamic patriarchal practices, and are oriented towards the protection of honor (hifz al-‘ird). The harmonization of these two systems is possible through the integration of the principle of Maqashid Syariah (the objectives of Sharia), which provides theological legitimacy for the contemporary efforts to combat TPKS. By optimizing the flexible Ta’zir punishment, Islamic Law can accommodate a more adaptive model of proof and victim recovery, aligned with the spirit of contemporary restorative justice.